Pemanfaatan Limbah Kotoran Dan Urine Sapi Perah Sebagai Penghasil Energi Alternatif Dan Pupuk Organik - Al Haris, Muhammad Fuad; Hidayat Kusuma, Dedy; Rahimi Bachtiar, Riza (Universitas Nusantara PGRI Kediri, 2022)
Kaligondo Village is an area that is a center for Small and Medium Enterprises (SMEs) engaged in the dairy farming sector in Genteng District, Banyuwangi. Where many people work as dairy farmers starting in 2001. The increasing need for fresh milk in the Banyuwangi area and the partnership between dairy farmers in Kaligondo Village and the national dairy company